Psychological factors outmatched morphological markers in predicting limitations in activities of daily living and participation in patients with lumbar stenosis - Quack; Boecker, M.; Mueller, C. A.; Mainz; Geiger, M.; Heineman, A. W.; El Mansy, Y.; Betsch, Marcel (BMC Musculoskeletal Disorders, 2019)
Background: Recent demographic changes have led to a large population of older adults, many of whom experience degenerative disc diseases. Degenerative lumbar spinal stenosis (DLSS) is associated with considerable discomfort and limitations in activities of daily living (ADL). Symptomatic DLSS is one of the most frequent indications for spinal surgery. The aim of this study was to identify sociodemographic variables, morphological markers, depression as well as fear of movement that predict ADL performance and participation in social life in patients with DLSS. Methods: Sixty-seven patients with DLSS (mean age 62.5 years [11.7], 50.7% females) participated in the study. Predictor variables were age, gender, duration of disease, three morphological markers (severity of the lumbar stenosis, the number of affected segments and presence of spondylolisthesis) as well as self-reported depression and fear of movement. Dependent variables were pain interference with the performance of ADLs, ADLs and participation in social life. Correlations between predictor and dependent variables were calculated before stepwise, linear regression analyses. Only significant correlations were included in the linear regression analyses. Results: Variance explained by the predictor variables ranged between 12% (R2 =.12; pain interference-physical) and 40% (R2 =.40; ADL requiring lower extremity functioning; participation). Depression and fear of movement were the most powerful predictors for all dependent variables. Among the morphological markers only stenosis severity contributed to the prediction of ADLs requiring lower extremity functioning. Conclusion: Depression and fear of movement were more important predictors of the execution of ADLs and participation in social life compared to morphological markers. Elevated depressive symptoms and fear of movement might indicate limited adaptation and coping regarding the disease and its consequences. Early monitoring of these predictors should therefore be conducted in every spine centre. Future studies should investigate whether psychological screening or a preoperative psychological consultation helps to avoid operations and enables better patient outcomes.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Depression; Fear of movement; Lumbar stenosis; Morphological markers; Outcome; Predictors; Psychological factors